The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15826/analitika.2015.19.2.013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instability of monoalkyl esters of phthalic acid during their gas chromatographic separation

Abstract: Поступила в редакцию 20 мая 2015 г., после доработки 11 июня 2015 г.Моноалкиловые эфиры бен зол-1,2-дикарбоновой (фта левой) кислоты являются основными продуктами метаболизма (частичного гидролиза) диалкил фталатов, широко применяющихся в ка-честве пластификаторов полимер ных композиций. Проверка возможностей газохроматографиче-ского и хро ма то-масс-спек т рометри чес кого анализа простейших моноалкиловых (С 1 -С 7 ) эфиров показала, что эти соединения тер ми чески нестабильны и разла га ются в хроматографиче… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…insufficiently characterized by analytical parameters up to present. One of such groups appeared to be the acidic esters of polycarboxylic acids, including alkyl esters of benzene-1,2-dicarboxylic acid (monoalkyl phthalates) that stimulated determination of their MS and GC analytical parameters [20] in comparison with the data for their much better characterized structural analoguesdialkyl phthalates. Rather unexpectedly it was found that monoalkyl phthalates appeared to be unstable at standard conditions of GC separation.…”
Section: Features Of Gc Separation Of Monoalkyl Phthalatesmentioning
confidence: 99%
See 4 more Smart Citations
“…insufficiently characterized by analytical parameters up to present. One of such groups appeared to be the acidic esters of polycarboxylic acids, including alkyl esters of benzene-1,2-dicarboxylic acid (monoalkyl phthalates) that stimulated determination of their MS and GC analytical parameters [20] in comparison with the data for their much better characterized structural analoguesdialkyl phthalates. Rather unexpectedly it was found that monoalkyl phthalates appeared to be unstable at standard conditions of GC separation.…”
Section: Features Of Gc Separation Of Monoalkyl Phthalatesmentioning
confidence: 99%
“…It is the unambiguous indication of thermal instability of monomethyl phthalate at conditions of GC separation, and its main decomposition product is phthalic anhydride. The same process can be assumed for other monoalkyl phthalates having the higher boiling points than monomethyl ester, and, hence, the higher retention temperatures [20]:…”
Section: Features Of Gc Separation Of Monoalkyl Phthalatesmentioning
confidence: 99%
See 3 more Smart Citations